2014
DOI: 10.1136/bmjspcare-2013-000535
|View full text |Cite
|
Sign up to set email alerts
|

Should we involve terminally ill patients in teaching medical students? A systematic review of patient's views

Abstract: An assumption that clinical undergraduate medical teaching involving terminally ill patients may be too burdensome is not reflected overall in studies that have sought the views of the patients themselves. Understanding the patient's perspective provides a number of practical points in relation to how clinical teaching should be adapted in this patient group; for example, using smaller student group sizes; direct supervision if physical examination performed; short encounters with multiple patients rather than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…There has been concern that involving patients with advanced illness (and their families) with teaching will place pressure and burden on the patients, students and nursing staff. However, research has shown that patients with advanced illness value seeing medical students for altruistic reasons and are willing to be involved in teaching (Finlay et al 2005;Gadoud et al 2012;Hayes 2012;Harris et al 2015). Smaller students groups and shorter teaching sessions are preferred by patients (Finlay et al 2005;Arolker et al 2010;Hayes 2012), with clear indication that they are free to decline (Hayes 2012).…”
Section: Tip 1 Compulsory (And Integrated Across the Course)mentioning
confidence: 99%
“…There has been concern that involving patients with advanced illness (and their families) with teaching will place pressure and burden on the patients, students and nursing staff. However, research has shown that patients with advanced illness value seeing medical students for altruistic reasons and are willing to be involved in teaching (Finlay et al 2005;Gadoud et al 2012;Hayes 2012;Harris et al 2015). Smaller students groups and shorter teaching sessions are preferred by patients (Finlay et al 2005;Arolker et al 2010;Hayes 2012), with clear indication that they are free to decline (Hayes 2012).…”
Section: Tip 1 Compulsory (And Integrated Across the Course)mentioning
confidence: 99%
“…20 This is challenging as the number of medical students is large, 21 and patients can sometimes be too unwell. However, the literature suggests patients want to be involved with teaching, if they are able to, 22 and junior doctors perceive that contact with the dying is imperative while at medical school. 23 It is surprising that medical students are generally required to be involved in one or more births, yet educational practice at the conclusion of life is so different.…”
Section: Patient Contactmentioning
confidence: 99%
“…15 Available guidelines and standards are general and fail to provide detail on the particular issues associated with involving this population. 1,2,16,17 There is limited literature on involvement in other palliative care settings, for example, education [18][19][20] or service provision. [21][22][23][24][25] The need for this review is therefore apparent, to promote more effective involvement in palliative care research, for the benefit of all, including clinicians, academics and patients/carers.…”
Section: Introductionmentioning
confidence: 99%